Chinese Phytopharmacology in dermatology - A Systematic Review - Jorge Magalhães Rodrigues; Catarina Santos; Victor Ribeiro; Anna Alvarenga; Rosa Vilares Santos (Elsevier, 2023)
Background: Dermatologic diseases are one of the most frequent health conditions. The impact on the quality of life of patients is evident and the negative effects on health can range from psychological and physical incapacity to even death. Because of the serious impact that dermatologic diseases can have on one's health, prevention and treatment of these conditions should be urgently included in global health strategies. Advancing scientific knowledge about traditional techniques has been gaining acknowledgement due to the contributions they can provide to global health. Objective: This study aims to analyse the current evidence on the effectiveness of traditional Chinese phytopharmacology (herbal medicine) on dermatologic conditions and to inform potential applications within western healthcare settings. Methodology: A systematic literature search was conducted in PubMed, Cochrane, Science Direct and Scielo databases to identify randomized clinical trials on Chinese herbal medicine for dermatologic conditions. Studies with low or moderate quality were excluded. Results: Our literature search yielded 151 studies, 135 after the removal of duplicates. After title and abstract screening, 38 studies were selected for retrieval. Full-text and quality assessment was performed on 33 studies, and 18 studies were included in the final analysis. Conclusions: Evidence suggests that Chinese phytopharmacology can be used as a complementary treatment for some dermatologic conditions. Major benefits seem to exist due to the presence of components that possess anti-fungal, anti-bacterial, anti-viral, and anti-inflammatory action, as well as immunomodulatory effects. More studies should be conducted to confirm the complementary benefits of Chinese phytopharmacology for dermatologic conditions. Registration: The protocol has been registered with the International Prospective Registry for Systematic Reviews (PROSPERO CRD42022308304).